Analisis Faktor-faktor Experiential Marketing yang mempengaruhi Keputusan Pembelian Konsumen terhadap Sepeda Motor Yamaha Mio di Universitas Muria Kudus - Winahyuningsih, Panca; Nugraheni, Fitri; Istikhomah, - (Lembaga Penelitian Universitas Muria Kudus, 2011)
Problem in this study were as follows: Does experiential marketing which consists of a variable Sense, Feel, Think, Act, Relate can influence purchasing decisions partially or multiple of the product Yamaha Mio at the University of Muria Kudus? And which variable has the highest impact in influencing purchasing decisions Yamaha Mio at the University of Muria Kudus? The results of regression analysis is known to have a positive and significant influence between variables Sense, Feel, Think, Act, and Relate partially based on the test results obtained for the variable Sense t test value of 2,317; Feel at 5,238; 2,095 Think; Act of 2,587; for Relate 2,084; and 1,986 greater than at table. This means a partial fifth variable consisted of Sense, Feel, Think, Act, and Relate has a positive and significant influence on purchase decisions Yamaha brand motor cycles are based on the F test results, obtained F tes of 12,047 is greater 2,32 than F table and a significance value of 0.000 is smaller than 0.05. From the results of regression analysis were the variables that have a Feel of greater influence than other variables, while its influence is jointly significant and positive influence on purchase decision variables, with contribution of 63,6 % and other variables beyond the study of 35,4 %.